2020
DOI: 10.1139/cgj-2018-0816
|View full text |Cite
|
Sign up to set email alerts
|

New method to calculate apparent phase velocity of open-ended pipe pile

Abstract: The apparent phase velocity of open-ended pipe piles after installation is difficult to predict owing to the soil-plug effect. This paper derives an analytical solution to calculate the apparent phase velocity of a pipe pile segment with soil-plug filling inside (APVPSP) based on the additional mass model. The rationality and accuracy of the developed solution are confirmed through comparison with the solution derived using the soil-plug Winkler model and experimental results. A parameter combination of the ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
23
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 75 publications
(23 citation statements)
references
References 23 publications
0
23
0
Order By: Relevance
“…Chen et al studied the dynamic characteristics and damage law of subway station [21]. Other scholars have also undertaken a lot of research on the dynamic response of various structures and foundations under earthquake using shaking table test and found that the depth and compactness of soil, the existence of structures, and the input parameters of shaking excitation have obvious effects on site liquefaction and dynamic response of structures and soil [22][23][24][25][26][27][28][29][30]. However, the above studies are aimed at the terrigenous sands, and there are few studies on coral sand at present.…”
Section: Introductionmentioning
confidence: 99%
“…Chen et al studied the dynamic characteristics and damage law of subway station [21]. Other scholars have also undertaken a lot of research on the dynamic response of various structures and foundations under earthquake using shaking table test and found that the depth and compactness of soil, the existence of structures, and the input parameters of shaking excitation have obvious effects on site liquefaction and dynamic response of structures and soil [22][23][24][25][26][27][28][29][30]. However, the above studies are aimed at the terrigenous sands, and there are few studies on coral sand at present.…”
Section: Introductionmentioning
confidence: 99%
“…Design of structures acquires accounting for how foundations (e.g., piles and rigid footings) interact with soil subjected to dynamic loading such as seismic loads and machine vibrations 1–4 . The common approach to this problem considered the foundation soil as an elastic, homogeneous, and isotropic half‐space, commonly abbreviated as elastic half‐space, and assumed a specific distribution of contact stresses below the rigid foundation.…”
Section: Introductionmentioning
confidence: 99%
“…Pile foundations are used to transfer static and dynamic loads to competent soil layers, which are commonly found below the groundwater table. Interaction of piles with their surrounding soil is particularly important for the analysis of dynamic soil‐foundation‐structure interaction problems; therefore, various approaches are proposed in the literature for modelling the response of piles subjected to harmonic loads . Early methods consider soil as single‐phase medium.…”
Section: Introductionmentioning
confidence: 99%